Efforts to Improve Vocabulary Learning Outcomes Through Word Game Methods with Media Pass Picture in Grade 2 Students at SDN 3 Mendenrejo - Winarti Winarti (Universitas Sebelas Maret, 2020)
The purpose of this research is to improve vocabulary learning through word game method with Pass Picture media in grade 2 students at SDN 3 Mendenrejo.Kabupaten Blora.This research is a class action research (PTK). Research is carried out in two cycles, with each cycle consisting of planning, execution of actions, observations, and reflections. The research subjects were grade 2 students at SDN 3 Mendenrejo with 16 students. Data sources come from teachers and students. Data collection techniques are by observation. Data analysis using descriptive data analysis techniques. Research procedures are interconnected. The results showed that through the application of word game methods through pass picture media can improve student vocabulary learning outcomes from pre-cycle I and from cycle I to cycle II. Improvement occurs in cycle I. vocabulary learning ability increases even if it is not optimal. The implementation of cycle II causes the ability to learn vocabulary to increase so that it can support a quality learning. The conclusion of this research is that the application of word game methods through Pass Picture can improve vocabulary learning skills in the learning of grade 2 students at SDN 3 Mendenrejo